«Perfil autorial en los sonetos de La Filomena (1621), de Lope de Vega» - Sánchez Jiménez, Antonio (My University, 2020)
Within Lope de Vega’s extensive sonnet production, the nine sonnets that he included in La Filomena (1621) can be examined to determine what kind of authorial voice they put forward and how it compares to the spirit of «metapoetic cancionero» that the cri- tics propose for the rest of the book. After summarizing secondary literature on Lope’s sonnets and on La Filomena, we analyze the sonnets in our corpus commenting their individual purpose, their common points, and, above all, the kind of authorial voice they build, which we examine focusing on the lyrical voice that enunciates them. This analysis allows us to present La Filomena not only as a “metapoetic cancionero”, but also as a neostoic one whose moral message stems from the sonnets dispositio.
Keywords: Lope de Vega; La Filomena; sonnets; self-fashioning; lyrical voice.